Palaeocene–Eocene miospores from the Chicxulub impact crater, Mexico. Part 1: spores and gymnosperm pollen. (2nd July 2020) - Smith, Vann; Warny, Sophie; Jarzen, David M.; Demchuk, Thomas; Vajda, Vivi
Abstract: In the summer of 2016, the International Ocean Discovery Program (IODP) Expedition 364 cored through the post-impact strata of the end-Cretaceous Chicxulub impact crater, Mexico. Core samples were collected from the post-impact successions for terrestrial palynological analysis, yielding a rare Danian to Ypresian high-resolution palynological assemblage. This record constitutes one of the first Palaeocene and Ypresian palynological assemblages from Central America or Mexico, representing a more coastal lowland palaeoenvironment than previous studies from mainland Mexico. Although the abundance of pollen and spores is very low in the Palaeocene carbonates, abundance increases in the more organic-rich shale layers representing the Palaeocene–Eocene Thermal Maximum (PETM) and later Ypresian. The spores and gymnosperm pollen identified from IODP 364, although rare compared to the angiosperm pollen, are a diverse mix of cosmopolitan taxa, as well as some characteristic of fossil Central American assemblages (e.g. Selaginellaceae), and others previously identified from the Paleogene northern Gulf of Mexico coastal plain. The assemblage generally indicates the presence of nearby moist to seasonally dry lowland tropical forest, with some taxa suggestive of higher elevation forests. Ephedroid pollen grains may be indicative of the presence of more arid conditions.